131I-Caerin 1.1 and 131I-Caerin 1.9 for the treatment of non-small-cell lung cancer - Liu, Na; He, Tiantian; Xiao, Zewei; Du, Juan; Zhu, Keke; Liu, Xiongying; Chen, Tongsheng; Liu, Wenjuan; Ni, Guoying; Liu, Xiaosong; Wang, Tianfang; Quan, Jiangtao; et al. (Frontiers in Oncology, 2022)
ABSTRACT Objective To investigate the effect of the 131I-labeled high-affinity peptides caerin 1.1 and caerin 1.9 for the treatment of A549 human NSCLC cells. Methods :① 3-[4,5-Dimethylthiazole-2-yl]-2,5-diphenyltetrazolium bromide (MTT) and plate clone formation assays were performed to confirm the in vitro anti-tumor activity of caerin 1.1 and caerin 1.9. ② Chloramine-T was used to label caerin 1.1 and caerin 1.9 with 131I, and the Cell Counting Kit 8 assay was performed to analyze the inhibitory effect of unlabeled caerin 1.1, unlabeled caerin 1.9, 131I-labeled caerin 1.1, and 131I-labeled caerin 1.9 on the proliferation of NSCLC cells. An A549 NSCLC nude mouse model was established to investigate the in vivo anti-tumor activity of unlabeled caerin 1.1, unlabeled caerin 1.9, 131I-labeled caerin 1.1, and 131I-labeled caerin 1.9. Results :① Caerin 1.1 and caerin 1.9 inhibited the proliferation of NSCLC cells in vitro in a concentration-dependent manner. The half-maximal inhibitory concentration was 16.26 µg/ml and 17.46 µg/ml, respectively, with no significant intergroup difference (P>0.05). ② 131I-labeled caerin 1.1 and 131I-labeled caerin 1.9 were equally effective and were superior to their unlabeled versions in their ability to inhibit the proliferation and growth of NSCLC cells (P>0.05). Conclusions: 131I-labeled caerin 1.1 and 131I-labeled caerin 1.9 inhibit the proliferation and growth of NSCLC cells and may become potential treatments for NSCLC.